2018
DOI: 10.1007/s11060-018-2802-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and survival of gliomatosis cerebri: a population-based cancer registration study

Abstract: Gliomatosis cerebri (GC) comprises a rare widespread infiltrating growth pattern of diffuse gliomas. We explored the incidence patterns and survival rates of GC in a population-based registration sample from the Surveillance, Epidemiology and End, Results database (1973-2012). GC cases (n = 176) were identified based on their International Classification of Diseases in Oncology (ICD-O-3) morphology code (9381). We calculated age-adjusted incidence rates (AIR) and evaluated temporal trends. Survival was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
1
19
1
Order By: Relevance
“…Radiotherapy has been attributed efficacy for GC treatment in case studies as well as retrospective studies containing a variety of radiation protocols [10,[24][25][26]. In contrast, studies with larger patient numbers failed to evidence the beneficial impact of radiotherapy on OS in GC patients [11,27,28]. Furthermore, no association between radiotherapy dose/ volume and OS has been established until now [10,29].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy has been attributed efficacy for GC treatment in case studies as well as retrospective studies containing a variety of radiation protocols [10,[24][25][26]. In contrast, studies with larger patient numbers failed to evidence the beneficial impact of radiotherapy on OS in GC patients [11,27,28]. Furthermore, no association between radiotherapy dose/ volume and OS has been established until now [10,29].…”
Section: Discussionmentioning
confidence: 99%
“…of 1648 patients found that seizures, associated with temporal lobe involvement, were present in roughly half of all patients; headache, associated with increased ICP, in 36% of patients; cognitive decline, associated with wide spread disease, in 32%; focal motor deficits, associated with motor cortex involvement, in 32%; and gait abnormalities, associated with cerebellar involvement, in 15% [4] . Rare, but important, complaints include blurred vision due to tumor involving of the optic nerves and pathways, cranial nerve palsies via involvement of the brainstem, and atypical parkinsonian syndromes via involvement of the basal ganglia [4 , 5] . The clinical exam findings and imaging/anatomical correlates of this case include left-sided weakness corresponding with involvement of the right paracentral lobule and corticospinal tract and global headache that was most likely related to increased ICP as evidence by diffuse effacement of the sulci and fissures.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Her extensive involvement evidenced by imaging suggests a gliomatosis cerebri growth pattern. Gliomatosis cerebri refers to an extensive and invasive growth pattern that involves at least three contiguous lobes and typically resembles a low-grade lesion radiologically (e.g., non-contrast enhancing), but is associated with a poor prognosis [1]. Until recently, it was classified separately within gliomas, but molecular studies did not warrant separation [2].…”
Section: Discussionmentioning
confidence: 99%